Modernizing Your Windows Applications with the Windows App SDK and WinUI : Expand your desktop apps to support new features and deliver an integrated Windows 11 experience /: Expand your desktop apps to support new features and deliver an integrated Windows 11 experience. (2022) - Pagani, Matteo; Plogas, Marc
No abstract available